Determinan Kepatuhan Pengobatan Penderita Hipertensi Usia 20-44 Tahun di Puskesmas Oesapa Kota Kupang - Yuliana Dewi Sartika Iwa; Afrona E.L. Takaeb; Eryc Z. Haba Bunga (Yayasan Literasi Sains Indonesia, 2025)
Hypertension is a disease that causes blood pressure in the blood vessels to increase above the normal limit, namely 120/80 mmHg. Hypertension cases in Oesapa in 2022 will be 4,985 cases, in 2023 there will be 4,625 cases and the majority of patients suffering from hypertension are patients 20-44 years old. One of the causes of the high number of hypertension cases is due to patient non-compliance in undergoing hypertension treatment. This study aims to analyze factors related to treatment compliance, namely knowledge, motivation to seek treatment, family support, the role of health workers, and ownership of health insurance. This type of research is quantitative with a cross sectional approach design. This research was conducted in the Oesapa Community Health Center Work Area in August 2024 with a total of 84 respondents suffering from hypertension aged 20-44 years. The data analysis technique uses the Chi-square statistical test. The results showed that knowledge, motivation, family support, the role of health workers has a significant relationship with treatment compliance. This study concludes that knowledge, motivation to seek treatment, family support, and the role of healthcare providers are associated with the adherence to medication treatment among hypertensive patients aged 20-44 years. Based on the research findings, it is recommended that regular health education be provided to working-age hypertensive patients to improve their knowledge about hypertension and the importance of treatment. For future research, it is suggested to develop studies on factors that can influence medication adherence by exploring other simpler factors and using different methods.